Cytokine-Leukotriene Receptor Interactions - Marek Rola-Pleszczynski; Jana Stankova (The Scientific World Journal)
Biochemical and pharmacological studies have identified the structure of leukotrienes, the pathways that lead to their synthesis, and the signaling events they trigger when they interact with their cognate receptors. A privileged interaction exists between these lipid mediators and another group of molecules essential for inflammation and immune modulation, namely, cytokines. Whereas leukotrienes can trigger the synthesis and release of selected cytokines in distinct cell populations, many cytokines can affect cellular responsiveness to leukotrienes by modulating leukotriene receptor expression. As we progressively begin to unravel these complex interactions, new areas of cell-cell communication and eventual therapeutic interventions will emerge.